Conformational Selectivity of Merocyanine on Nanostructured Silver Films: Surface Enhanced Resonance Raman Scattering (SERRS) and Density Functional Theoretical (DFT) Study - Das, Abhishek; Chadha, Ridhima; Mishra, Amaresh; Maiti, Nandita (Frontiers in Chemistry, 2022)
In this study, detailed structural and vibrational analysis of merocyanine has been investigated using Raman, surface enhanced Raman scattering (SERS) and surface enhanced resonance Raman scattering (SERRS). The Raman, SERS and SERRS studies aided by density functional theoretical (DFT) calculations clearly established the prevalence of the trans- and cis- conformers of the protonated form of merocyanine (MCH+) in solid and acetonitrile solution. The binding characteristics of merocyanine adsorbed on nanostructured silver-coated films (SCFs) were investigated using excitation-dependent SERS, concentration-dependent SERRS and DFT studies. The conformers of merocyanine involved in the surface adsorption processes were recognized. The prominent marker bands observed at 1538 (ethylenic C=C stretch) and 1133 cm-1 (pyridinium C-N stretch) in the Raman spectrum of merocyanine in acetonitrile shifted to 1540 and 1126 cm-1, respectively on the nanostructured SCFs. The shift in the marker bands is associated with either the preferential binding of selective conformer or change in resonance equilibrium between the benzenoid and quinoid forms. The excitation wavelength dependent SERS spectrum infers that in addition to the major contribution from the electromagnetic enhancement, chemical (resonance) effect leads to the amplification of the 1540 cm-1 band. The concentration-dependent SERRS study showed maximum enhancement for the nanostructured SCFs functionalized with 1 µM concentration of merocyanine, indicative of monolayer coverage. For lower concentrations of merocyanine, the SERRS signal intensity reduced without any alteration in the peak positions. The SERRS study thus, revealed sub-nanomolar (0.1 nM) sensing of merocyanine using nanostructured SCFs with the analytical enhancement factor (AEF) of ~ 1010 for the 1126 cm-1 and 1540 cm-1 Raman bands for MC concentration of 0.1 nM. In this study, combination of SERRS and DFT have clearly established the predominance of trans-MCH+ on the nanostructured silver surface with minor contribution from cis-MCH+, which remain exclusively bound to the surface via the phenoxyl ring O atom. This conformational surface selectivity of geometrical isomers of merocyanine using nanostructured surfaces can be further explored for energy efficient and economical separation of geometrical isomers.